Archetypes in Ragini Upadhyay's Paintings - Hamal, Koshal (Journal of Fine Arts Campus, 2023)
Archetype signifies the reflection of primordial symbols belonging to myth, culture, or rituals in the work of an artist from his or her collective unconscious. The main aim of this study is to reveal the archetypal character in the works of Ragini Upadhyay. The most recurring motifs, such as Bell, Kumari, Kali, Kamadhenu, Tulsi, Shiva Linga, Shiva, Buddha, Stupa, Lotus, Temples, and Garuda, are some of the key primordial symbols presented in her works; all of these symbols are associated with Hindu myth, culture, and rituals. The artist comes from a Brahmin family background, a caste within Hindu culture. Thus, there is a huge impact of Hinduism in her paintings, which she expresses in the form of art through her collective unconscious. This study is qualitative in nature and attempts to give a solution to a problem through observation and interpretation of the archetypes and paintings associated with this research topic.